Suppression of inflammation by ethanol extract of Clausena lansium via modulation of TLR4/MYD88/TRAF6 signaling pathway in RAW 264.7 macrophages. (April 2019) - Huang, Guihong; Li, Juan; Li, Wanlian; Liu, Tianxu; Jiang, Guojun; Wu, Ting; Zou, Yong; Huang, Junhe; Tao, Liqun; Zhu, Zhaoming; Yue, Jiakui; Zhang, Xiaoling; et al.
The fruit and root of Clausena lansium are remedy for bronchitis in oriental traditional medicine. Extracts from Clausena lansium are reported to have antioxidant, anti-inflammatory, and anticancer activities. This study is designed to investigate whether the ethanol extract of Clausena lansium (Lour.) Skeels could inhibit the lipopolysaccharides (LPS)-induced inflammatory in RAW 264.7 macrophages and the underlining mechanisms. Enzyme-linked immunosorbent assay (ELISA) and reverse transcription polymerase chain reaction (RT-PCR) are used to detect the secretion of tumor necrosis factor alpha (TNF-α) protein and expression of TNF-α mRNA, respectively. RT-PCR and Western blotting are used to determine the mRNA and protein levels of TLR4, MYD88, and TRAF6, respectively. The extract of Clausena lansium suppressed the expression and secretion of TNF-α, which is released by RAW 264.7 cells after LPS induction. Meanwhile, the expression of TLR4, MYD88, and TRAF6 are decreased by extracts from Clausena lansium . Meanwhile, NBP2-29328, an inhibitor of MYD88, synergistically enhances the inhibiting effect of extract from Clausena lansium . The results imply that ethanol extract from Clausena lansium attenuate macrophage-mediated inflammation and TLR4/MYD88/TRAF6 pathway is its potential target.